Patterns of alcohol use among early head and neck cancer survivors: A cross-sectional survey study using the alcohol use disorders identification test (AUDIT). (August 2021) - Teckie, Sewit; Wotman, Michael; Marziliano, Allison; Orner, David; Yi, Jungen; Mulvany, Colm; Ghaly, Maged; Parashar, Bhupesh; Diefenbach, Michael A.
Highlights: Current rates of alcohol use in HNC survivors are concerning. Consumption decreases after treatment but then steady rises to surpass baseline levels. Interventions to reduce alcohol consumption are urgently needed. Abstract: Objective: Alcohol use among survivors of head and neck cancer (HNC) negatively impacts patient outcomes and is an important risk factor for recurrent and second primary tumors. Despite recommendations from several cancer societies, alcohol consumption remains a common problem in this population. Methods: A cross-sectional study was performed with the Alcohol Use Disorders Identification Test (AUDIT) Self-Report questionnaire. Patients with HNC completed surveys at pre-treatment and follow-up appointments every 3–6 months for at least 2-years after treatment. Results: 796 surveys were available for analysis. Most participants were male (75.7%) and had either oropharyngeal (34.5%) or laryngeal (16.7%) cancer. The percentage of alcohol drinkers decreased from 56.1% at pre-treatment to 40.4% at 0–3 months post-treatment, but then increased and surpassed baseline levels by 24 + months post-treatment (64.4%, p  = 0.0079). Concurrently, moderate drinkers (AUDIT = 1 – 3) decreased from 34.2% at pre-treatment to 25.2% at 0–3 months post-treatment, but then increased and surpassed baseline levels at 24 + months post-treatment (39.7%, p  = 0.0129). Trends among heavy (AUDIT > 3), and heaviest (AUDIT > 6) drinkers were similar, but not statistically significant. At 24 + months post-therapy, we observed a statistically significant increase in female users (39.1% to 63.2%, p  = 0.0213) and moderate drinkers < 55 years old (43.4% to 61.9%, p  = 0.0184). Conclusion: Alcohol consumption in survivors of HNC transiently decreases in the immediate months after treatment, but then increases and remains largely stable by 24 months. This pattern is particularly concerning and highlights the need for timely interventions.